Viewpoint diversity in public health - VanderWeele, Tyler J. (Frontiers in Public Health, 2023)
Schools of public health are often situated within universities but not infrequently also function as public health advocacy organizations. Viewpoint diversity on many issues is often limited within schools of public health and does not reflect the diversity one finds in society more generally. It is argued that welcoming, and even seeking out, viewpoint diversity within public health would contribute to understanding and knowledge, to the training public health leaders and academics who can serve the whole of society, and to working together across ideological lines to better contribute to population health.